Pengembangan Booklet Digital Materi Keanekaragaman Hayati Kelas X - Kencana Hastin Prameswati; Much. Fuad Saifuddin (BIOEDUSCIENCE, 2022)
Background: Distance learning requires learning media to help students understand the material. Digital booklets are an alternative to teaching biodiversity through visualization. This study aimed to determine the feasibility of digital booklets for class X biodiversity materials. Methods: This Research and Development use the ADDIE model. The product is validated by expert validators, material experts, and teachers. Product trials on students were divided into two groups, namely small groups (10 students) and large groups (30 students). Results:  The results of the product assessment meet the very feasible category with scores of 91.67% (media experts), 61.25% (material experts), and 81.25% (teachers). The small group test on students obtained a percentage of 96%, and the big group test with a percentage of 95.33%. Conclusions: The digital booklet learning media product is suitable for class X biodiversity learning.